Del furioso cañoneo al eco de Bolívar: guerra, ciudad y sonoridad en Lima, 1819-1826 - Sánchez, Susy (2016)
This article examines the soundscape, both commemorative and disruptive, experienced in the city of Lima during the War of Independence, focusing on the sounds produced by church bells and cannons. Even though, in Lima, patriots and royalists never fought a pitched battle, the war resoundingly marked the city’s aural environment. Disruptive noise emitted by church bells and cannons  during the war greatly exceeded in intensity and duration the commemorative sounds sponsored by the independent government, and even had the power to change it dramatically.